2018
DOI: 10.1097/mnh.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

The systems biology of uric acid transporters

Abstract: Purpose of review Uric acid homeostasis in the body is mediated by a number of SLC and ABC transporters in the kidney and intestine, including several multispecific ‘drug’ transporters (e.g., OAT1, OAT3, and ABCG2). Optimization of uric acid levels can be viewed as a ‘systems biology’ problem. Here, we consider uric acid transporters from a systems physiology perspective using the framework of the ‘Remote Sensing and Signaling Hypothesis.’ This hypothesis explains how SLC and ABC ‘drug’ and other transporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 66 publications
(114 reference statements)
0
40
0
2
Order By: Relevance
“…Excretion of UA is mainly determined by the balance between renal reabsorption and secretion, and the role of various urate transporters has been debated [8]. Usually, GLUT9, URAT1, OAT1, and OAT3 are the main transporters regulating renal urate handling, while ABCG2 appears to regulate intestinal transport [19]. For example, Vibha Bhatnagar et al pointed out that Chronic Renal Insufficiency Cohort data showed that GLUT9 played a much less significant role than ABCG2 in this subset of patients with CKD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Excretion of UA is mainly determined by the balance between renal reabsorption and secretion, and the role of various urate transporters has been debated [8]. Usually, GLUT9, URAT1, OAT1, and OAT3 are the main transporters regulating renal urate handling, while ABCG2 appears to regulate intestinal transport [19]. For example, Vibha Bhatnagar et al pointed out that Chronic Renal Insufficiency Cohort data showed that GLUT9 played a much less significant role than ABCG2 in this subset of patients with CKD [20].…”
Section: Discussionmentioning
confidence: 99%
“…SLC22 transporters are among the best known drug transporters (OAT1, OAT3, OCT1, OCT2), but it is now clear from knockouts (including genome scale metabolic reconstructions of the knockouts) and human SNPs that their endogenous substrates include many metabolites, signaling molecules, gut microbiome products, antioxidants, vitamins and other physiologically important molecules 1,2,6065 . Several metabolic diseases are associated with mutations or SNPs in SLC22 transporters 2,17,66 . There is a growing amount of evidence that SLC22 transporters such as OAT1 and OAT3 are important in the movement of metabolites through the gut-liver-kidney axis 10,12 .…”
Section: Resultsmentioning
confidence: 99%
“…These homeostatic networks can be sited within a single organ or involve several organs 20 . For example, three multi-specific transporters (OAT1, OAT3 and ABC subfamily G member 2 (ABCG2)) work closely with two limited-specificity transporters (URAT1 (also known as SLC22A12) and GLUT9 (also known as SLC2A9)) to control urate homeostasis 21 . In the absence of end-stage renal disease (ESRD), the bulk of urate handling in the kidney is carried out by these and several other transporters.…”
Section: Remote Sensing and Signalingmentioning
confidence: 99%